Benefits of demand response with controllable loads in smart grid : a case study of Pattaya City, Thailand - Tanit Chanraksa; Singh, Jai Govind; Weerakorn Ongsakul; Loc Thai Nguyen; PEA; AIT Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Low participation of demand response programs (DRPs) in both customers and programs launched by electric utility in Thailand nowadays. In order to motive a stakeholder, all benefits in both financial and non-financial should be guided. With lots of DRPs launched utility, customer may choose one DRPs to maximize their benefits. This work applies HiVE Enerkey which is the smart artificial intelligence system and type of horne energy management to control the appliances in two type of controllable loads, shiftable load such as electric vehicles (EVs) and thermostat load such as air conditioner (At") with two different DRPs which are critical peak pricing and emergency demand response programs. The Danish distribution grid is selected as the case study. The impact of EV s penetration is analyzed first. Then, the benefits for customers and utility are presented. The results show that critical peak pricing can allow maximum financial benefit for participant, and both customers and utility can also benefit from DRP shown in term of financial and non-financial benefits. The load flow analysis and simulation modelling are carried out by MATLAB software.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2019
Keywords: Smart power grids -- Thailand -- Pattaya -- Case studies